2012
DOI: 10.1111/j.1462-2920.2012.02703.x
|View full text |Cite
|
Sign up to set email alerts
|

A third mode of surface‐associated growth: immobilization of Salmonella enterica serovar Typhimurium modulates the RpoS‐directed transcriptional programme

Abstract: Although the growth of bacteria has been studied for more than a century, it is only in recent decades that surface-associated growth has received attention. In addition to the well-characterized biofilm and swarming lifestyles, bacteria can also develop as micro-colonies supported by structured environments in both food products and the GI tract. This immobilized mode of growth has not been widely studied. To develop our understanding of the effects of immobilization upon a food-borne bacterial pathogen, we u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 89 publications
(165 reference statements)
3
18
3
Order By: Relevance
“…This observation is in contrast with the results published by Knudsen et al (2012), where for S. Typhimurium grown at 25°C in gel cassettes, the lag phase for colonies is significantly longer than the one for planktonic cells. Differences between Knudsen et al (2012) and the present work can probably be accounted to the use of different experimental set-ups.…”
Section: Lag Phasecontrasting
confidence: 85%
See 1 more Smart Citation
“…This observation is in contrast with the results published by Knudsen et al (2012), where for S. Typhimurium grown at 25°C in gel cassettes, the lag phase for colonies is significantly longer than the one for planktonic cells. Differences between Knudsen et al (2012) and the present work can probably be accounted to the use of different experimental set-ups.…”
Section: Lag Phasecontrasting
confidence: 85%
“…This observation is in contrast with the results published by Knudsen et al (2012), where for S. Typhimurium grown at 25°C in gel cassettes, the lag phase for colonies is significantly longer than the one for planktonic cells. Differences between Knudsen et al (2012) and the present work can probably be accounted to the use of different experimental set-ups. As stated in this study, Boons et al (2013) observed similar lag phase durations in both liquid systems and different gelled systems for S. Typhimurium and E. coli at 23.5°C at low salt concentrations.…”
Section: Lag Phasecontrasting
confidence: 85%
“…Exceptionally, lag duration of cells growing on a gel surface was found longer than in planktonic growth at 25°C (Knudsen et al, 2012). Variation in composition among the used model systems in other studies and in this study could be the key for the existence or not of differences at the lag phase between planktonic and surface growth.…”
Section: Accepted Manuscriptmentioning
confidence: 76%
“…Bacterial biofilms have been intensively studied because they adversely affect humans in medical and industrial settings (for reviews, see references 7, 8, and 9). Throughout the history of microbiology, bacterial colonies have been used for diagnostic and enumerative ends but have rarely been objects of scientific scrutiny for their own sake (10)(11)(12)(13)(14)(15). However, the available data show that there are many similarities between biofilms and colonies.…”
mentioning
confidence: 99%